Analysis of Entrepreneurship Skills of Nini Kebab and Keripik Pak Rahul MSMEs at Polbeng Business Expo Chapter II - Alya, Martha; Astari, Yanisha Dwi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the entrepreneurship skills demonstrated by two Micro, Small, and Medium Enterprises (MSMEs), namely Nini Kebab and Keripik Pak Rahul, during their participation in the Polbeng Business Expo Chapter II. MSMEs play a strategic role in Indonesia’s economic development by contributing to employment creation, income distribution, and regional economic resilience. However, increasing competition, digital transformation, and changing consumer behavior require MSME actors to continuously strengthen their entrepreneurial competencies. This research aims to examine how creativity, communication, and promotional skills are applied in a real-market simulation context through an experiential learning platform. A descriptive quantitative approach was employed by distributing structured questionnaires to 100 respondents who interacted directly with the MSMEs during the expo. Data were analyzed using descriptive statistics with the assistance of SPSS. The findings indicate that both MSMEs demonstrate good overall entrepreneurship skills, with communication skills receiving the highest average score, followed by creativity and promotional skills. Nini Kebab showed stronger performance in digital promotion and customer engagement, while Keripik Pak Rahul demonstrated consistency in service quality and operational management. The results highlight the importance of experiential learning activities, such as business expos, in strengthening practical entrepreneurial skills among MSMEs. This study contributes to entrepreneurship education literature by providing contextual evidence of skill application within a campus-based business expo and offers practical implications for MSME development programs and future expo design.